Implementation of Electronic Government (E-Government) and Bureaucracy Reform to Achieve Good Governance - Maria Jose de Carvalho Soares; Guido Gonsalves Moniz; Leonito Ribeiro (IHSA Institute, 2022)
In this era of modernization, the dissemination of information and public transparency are crucial, this phenomenon can be seen through the high number of people in the communities responding to information and the efforts to get transparent information. This can be used as a base to keep track of the government’s working progress and to balance public awareness. Therefore, the government is trying to find various ways to enable people to access information easily so the public can track the government’s overall performance. Good governance is a clean government, a process that can guarantee the realization of human rights in a manner essentially free of abuse and corruption and with due regard to the rule of law. The implementation of electronic government (e-Government) in Timor-Leste, as a form of bureaucratic reform to achieve good governance, began in 2011 using the 2011-2030 Planu Estratejia Dezenvolvimentu Nasional as the foundation for achieving reasonable control. In Planu Estratejia Dezenvolvimentu Nasional 2011-2030, declares that one of the challenges faced by the Government of Timor-Leste after gaining independence is the vulnerability of government institutions so that e-Government plays an essential role in connectivity between the community and the government